2018
DOI: 10.1175/jamc-d-16-0408.1
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Power Outage Impacts from Future Hurricane Sandy Scenarios

Abstract: Hurricane Sandy (2012, referred to as Current Sandy) was among the most devastating storms to impact Connecticut’s overhead electric distribution network, resulting in over 15 000 outage locations that affected more than 500 000 customers. In this paper, the severity of tree-caused outages in Connecticut is estimated under future-climate Hurricane Sandy simulations, each exhibiting strengthened winds and heavier rain accumulation over the study area from large-scale thermodynamic changes in the atmosphere and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Computer models and simulations provide key insights as storms are forecasted. Power outage estimation models exist for tropical cyclones and hurricanes [11][12][13][14], thunderstorms [15], and various weather and vegetation inputs [16][17][18]. Han et al [12] recognized that accurate storm estimates are necessary to have the proper crews in place to make restoration as efficient as possible.…”
Section: Resiliencymentioning
confidence: 99%
See 3 more Smart Citations
“…Computer models and simulations provide key insights as storms are forecasted. Power outage estimation models exist for tropical cyclones and hurricanes [11][12][13][14], thunderstorms [15], and various weather and vegetation inputs [16][17][18]. Han et al [12] recognized that accurate storm estimates are necessary to have the proper crews in place to make restoration as efficient as possible.…”
Section: Resiliencymentioning
confidence: 99%
“…The ABM presented in [25] can be utilized, as shown in this study, to aid emergency managers in Resiliency Zones 1-3. As the storm is predicted in Zone 1, the weather forecasts can be utilized to predict the expected outages [11,15,17,18,26], which can then allow emergency managers to begin understanding the necessary resources. As the storm is better understood in Zones 2 and 3, the ABM can be run with the updated outage predictions to see how the predicted restoration time would change with available resources.…”
Section: Resiliencymentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting products are intended to serve as guidelines for an effective response. For example, the anticipation of a major hazard that may result in the closure of roadways, cancellation of events, curtailment of aircraft and transit operations, and loss of power informs the planned response [64]. The particular responses and their effectiveness (e.g., real or suggested, such as in validation studies [65]) can then be monitored and reported via news outlets (online or otherwise) before and during impacts.…”
Section: Systems Interactionmentioning
confidence: 99%